HEALTH SCENARIO REGARDING CARE FOR NEONATES AFTER HOSPITAL ADMISSION - Medeiros, Melissa Santana; Batista, Maria Clara Crescêncio; Low, Sandra Trindade; Spinelli, Maria Benita Alves da Silva; Pereira Neta, Maria Joana; Cantarutti, Lêda Maria de Lima; Aguiar, Lucilene Rafael; Beserra, Maria Aparecida (Seven Editora, 2025)
Considering that the neonatal period represents a phase of high vulnerability to infant health, marked by biological, environmental, and social risks, the continuity of care after hospital discharge is a challenge for families and health services. This study aims to understand the continuity of care and follow-up of newborns after hospitalization. To this end, a descriptive, cross-sectional study with a quantitative approach was conducted in a referral outpatient clinic in the city of Recife/PE, with the participation of 11 caregivers of newborns previously hospitalized for more than 24 hours and under outpatient follow-up. Data collection was carried out using a structured questionnaire, including sociodemographic information, clinical data, and aspects of the post-discharge scenario, with the data analyzed using descriptive statistics. Thus, it was observed that the median age at admission was 17 days, with an average length of stay of 10 days, the main causes of hospitalization being infections and jaundice. It was identified that only 45.5% of families left the consultation with a scheduled follow-up appointment, and that 81.8% required unscheduled care. The difficulties reported involved insecurity in care, emotional overload, and socioeconomic barriers, while the solutions suggested included prior scheduling of consultations, clearer guidelines, and systematic use of the Child’s Health Record. It is concluded that the continuity of neonatal care after discharge presents clinical and social weaknesses, reinforcing the need for supervised professional follow-up. DOI: https://doi.org/10.56238/sevened2025.036-146